Commission of Enquiry on Monuments and Conditions of Service of Central Government Employers 1957-59 Report - Planning Commission (Planning Commission, 1957)
The terms of reference of the Commission will be as follows:— (i) examine the principles which should govern the structure of emoluments and conditions of service of the Central Government employees; (ii) consider and recommend what changes in the structure of emoluments and conditions of service of different classes of Central Government employees are desirable and feasible keeping in mind the considerations mentioned below; (iii) recommend, in particular, the extent to which benefits to Central Government employees can be given in the shape of amenities and facilities.
Programme Evaluation Organisation, Planning Organisation